Functionalization of Natural Fibres Textiles by Improvement of Nanoparticles Fixation on Their Surface (Journal of Fiber Bioengineering and Informatics, 2012)
Lignin is a natural polymer characterized by its ability to absorb ultraviolet rays and antibacterialproperties. Thanks to nano size, nanolignin deposited on the fabric surface does not cause colourchange, even though the lignin is originally dark. As a functional polymer it can be used as a naturalUV barrier and antibacterial agent in finishing process of protective textiles.The paper describes the study on the improvement of nanoparticle fixation on the lignocellulosic fabricsurface by the introduction of a binding agent in the finishing technology. Several binding agents withnanolignin solution were applied to the linen fabric and non-woven by padding method. Effectivenessof textile covering by functional nanoparticles was evaluated by UPF tests after ten washing cyclesand abrasion tests. The best nanolignin coating on the linen fabric surface durability was obtained forapplication of acrylic dispersion as a binding agent. The FTIR (Fourier Transform Infrared) spectroscopywas applied for additional evaluation of linen fabrics covered by lignin nanoparticles.